Synthesis and characterization of novel BODIPYs and their antioxidant, antimicrobial, photodynamic antimicrobial, antibiofilm and DNA interaction activities - Can Karanlik, Ceren; Karanlik, Gurkan; Ozdemir, Sadin; Tollu, Gulsah; Erdogmus, Ali (WILEY, 2024)
In the current study, we synthesized and characterized new BODIPY derivatives (1-4) having pyridine or thienyl-pyridine substituents at meso-position and 4-dibenzothienyl or benzo[b]thien-2-yl moieties at 2-,6- positions. We investigated fluorescence properties and the ability to form singlet oxygen. In addition, various biological activities of BODIPYs such as DPPH scavenging, DNA binding/cleavage ability, cell viability inhibition, antimicrobial activity, antimicrobial photodynamic therapy (aPDT) and biofilm inhibition properties were performed. BODIPY derivatives BDPY-3 (3) and BDPY-4 (4) have high fluorescence quantum yields as 0.50 and 0.61 and O-1(2) quantum yields were calculated as 0.83 for BDPY-1 (1), 0.12 for BDPY-2 (2), 0.11 for BDPY-3 and 0.23 for BDPY-4. BODIPY derivatives BDPY-2, BDPY-3 and BDPY-4 displayed 92.54 +/- 5.41%, 94.20 +/- 5.50%, and 95.03 +/- 5.54% antioxidant ability, respectively. BODIPY compounds showed excellent DNA chemical nuclease activity. BDPY-2, BDPY-3 and BDPY-4 also exhibited 100% APDT activity against E. coli at all tested concentrations. In addition to these, they demonstrated a highly effective biofilm inhibition activity against Staphyloccous aureus and Pseudomans aeruginosa. BDPY-4 showed the most effective antioxidant and DNA cleavage activity, while BDPY-3 exhibited the most effective antimicrobial and antibiofilm activity.
Keywords: antimicrobial; antimicrobial photodynamic therapy; antioxidant; biofilm inhibition; BODIPY; cleavage; DNA binding; SINGLET OXYGEN; BIOFILM FORMATION; EXCITED-STATE; THERAPY; DERIVATIVES; DYES; PHOTOCLEAVAGE; INACTIVATION; FLUORESCENT; MECHANISM; Biochemistry & Molecular Biology; Biophysics